A novel and robust heterogeneous Cu catalyst using modified lignosulfonate as support for the synthesis of nitrogen-containing heterocycles - Lai, Bingbing; Ye, Meng; Liu, Ping; Li, Minghao; Bai, Rongxian; Gu, Yanlong (Beilstein Journal of Organic Chemistry, 2020)
A waste biomass, sodium lignosulfonate, was treated with sodium 2-formylbenzenesulfonate, and the phenylaldehyde condensation product was then used as a robust supporting material to immobilize a copper species. The so-obtained catalyst was characterized by many physicochemical methods including FTIR, EA, FSEM, FTEM, XPS, and TG. This catalyst exhibited excellent catalytic activity in the synthesis of nitrogen-containing heterocycles such as tricyclic indoles bearing 3,4-fused seven-membered rings, 2‑arylpyridines, aminonaphthalenes and 3-phenylisoquinolines. In addition, this catalyst showed to be recyclable and could be reused several times without significant loss in activity during the course of the reaction process.
Keywords: biomass; heterogeneous catalyst; immobilized copper catalyst; lignosulfonate; nitrogen-containing heterocycles; solid acid

(untitled) - Xie, F.; Lu, G.-P.; Xie, R.; Chen, Q.-H.; Jiang, H.-F.; Zhang, M. (ACS Catal., 2019)

(untitled) - Ma, Z.; Song, T.; Yuan, Y.; Yang, Y. (Chem. Sci., 2019)

(untitled) - Xie, C.; Niu, Z.; Kim, D.; Li, M.; Yang, P. (Chem. Rev., 2020)

(untitled) - Dai, X.; Wang, B.; Wang, A.; Shi, F. (Chin. J. Catal., 2019)

(untitled) - Hübner, S.; de Vries, J. G.; Farina, V. (Adv. Synth. Catal., 2016)

(untitled) - Wei, Z.; Shao, F.; Wang, J. (Chin. J. Catal., 2019)

(untitled) - Jin, T.; Hicks, M.; Kurdyla, D.; Hrapovic, S.; Lam, E.; Moores, A. (Beilstein J. Org. Chem., 2020)

(untitled) - Han, Y.; Wang, Z.; Xu, R.; Zhang, W.; Chen, W.; Zheng, L.; Zhang, J.; Luo, J.; Wu, K.; Zhu, Y.; Chen, C.; Peng, Q.; et al. (Angew. Chem., Int. Ed., 2018)

(untitled) - Sardarian, A. R.; Eslahi, H.; Esmaeilpour, M. (ChemistrySelect, 2018)

(untitled) - Deraedt, C.; Ye, R.; Ralston, W. T.; Toste, F. D.; Somorjai, G. A. (J. Am. Chem. Soc., 2017)

(untitled) - Liu, C.; Zhou, L.; Jiang, D.; Gu, Y. (Asian J. Org. Chem., 2016)

(untitled) - Zhu, Y.; Li, Z.; Chen, J. (Green Energy Environ., 2019)

(untitled) - Zhang, X.; Zhang, Z.; Wang, F.; Wang, Y.; Song, Q.; Xu, J. (J. Mol. Catal. A: Chem., 2013)

(untitled) - Sun, S.; Bai, R.; Gu, Y. (Chem. – Eur. J., 2014)

(untitled) - Lai, B.; Bai, R.; Gu, Y. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Lee, C. M.; Kubicki, J. D.; Fan, B.; Zhong, L.; Jarvis, M. C.; Kim, S. H. (J. Phys. Chem. B, 2015)

(untitled) - Wang, K.; Jia, Z.; Yang, X.; Wang, L.; Gu, Y.; Tan, B. (J. Catal., 2017)

(untitled) - Maggi, R.; Shiju, N. R.; Santacroce, V.; Maestri, G.; Bigi, F.; Rothenberg, G. (Beilstein J. Org. Chem., 2016)

(untitled) - Gao, S.; Luo, T.; Zhou, Q.; Luo, W.; Li, H.; Jing, L. (J. Colloid Interface Sci., 2018)

(untitled) - Parhizkar, J.; Habibi, M. H.; Mosavian, S. Y. (Silicon, 2019)

(untitled) - Jakab, E.; Faix, O.; Till, F.; Székely, T. (J. Anal. Appl. Pyrolysis, 1993)

(untitled) - Fiorani, G.; Perosa, A.; Selva, M. (Green Chem., 2018)

(untitled) - Li, S.; Liu, S.; Fu, Z.; Li, Q.; Wu, C.; Guo, W. (Surf. Interface Anal., 2017)

(untitled) - Xu, S.; Yin, C.; Pan, D.; Hu, F.; Wu, Y.; Miao, Y.; Gao, L.; Xiao, G. (Sustainable Energy Fuels, 2019)

(untitled) - Gunduz, H.; Kumbaraci, V.; Özkılıç, Y.; Tüzün, N. Ş.; Talinli, N. (ChemistrySelect, 2019)

(untitled) - Sakurai, H.; Koga, K.; Kiuchi, M. (Catal. Today, 2015)

(untitled) - Lai, B.; Huang, Z.; Jia, Z.; Bai, R.; Gu, Y. (Catal. Sci. Technol., 2016)

(untitled) - Lan, D.-H.; Chen, L.; Au, C.-T.; Yin, S.-F. (Carbon, 2015)

(untitled) - Li, H.; Cheng, R.; Liu, Z.; Du, C. (Sci. Total Environ., 2019)

(untitled) - Dong, X.; Ren, B.; Sun, Z.; Li, C.; Zhang, X.; Kong, M.; Zheng, S.; Dionysiou, D. D. (Appl. Catal., B, 2019)

(untitled) - Ghodsinia, S. S. E.; Akhlaghinia, B. (Green Chem., 2019)

(untitled) - Nemoto, T.; Harada, S.; Nakajima, M. (Asian J. Org. Chem., 2018)

(untitled) - Chen, S.; Ravichandiran, P.; El-Harairy, A.; Queneau, Y.; Li, M.; Gu, Y. (Org. Biomol. Chem., 2019)

(untitled) - Zheng, S.; Zhong, Q.; Mottamal, M.; Zhang, Q.; Zhang, C.; LeMelle, E.; McFerrin, H.; Wang, G. (J. Med. Chem., 2014)

(untitled) - Hackenberger, D.; Weber, P.; Blakemore, D. C.; Goossen, L. J. (J. Org. Chem., 2017)

(untitled) - Das, P.; Saha, D.; Saha, D.; Guin, J. (ACS Catal., 2016)

(untitled) - Shintani, R.; Misawa, N.; Takano, R.; Nozaki, K. (Chem. – Eur. J., 2017)

(untitled) - Kuzmina, O. M.; Steib, A. K.; Markiewicz, J. T.; Flubacher, D.; Knochel, P. (Angew. Chem., Int. Ed., 2013)

(untitled) - Donohoe, T. J.; Bower, J. F.; Basutto, J. A.; Fishlock, L. P.; Procopiou, P. A.; Callens, C. K. A. (Tetrahedron, 2009)

(untitled) - Colby, D. A.; Bergman, R. G.; Ellman, J. A. (J. Am. Chem. Soc., 2008)

(untitled) - Sheng, J.; Fan, C.; Ding, Y.; Fan, X.; Wu, J. (Chem. Commun., 2014)

(untitled) - Jin, Y.; Makida, Y.; Uchida, T.; Kuwano, R. (J. Org. Chem., 2018)

(untitled) - Wilson, T. A.; Koneru, P. C.; Rebensburg, S. V.; Lindenberger, J. J.; Kobe, M. J.; Cockroft, N. T.; Adu-Ampratwum, D.; Larue, R. C.; Kvaratskhelia, M.; Fuchs, J. R. (ACS Med. Chem. Lett., 2019)

(untitled) - Asako, T.; Suzuki, S.; Itami, K.; Muto, K.; Yamaguchi, J. (Chem. Lett., 2018)

(untitled) - Bertuzzi, G.; Pecorari, D.; Bernardi, L.; Fochi, M. (Chem. Commun., 2018)